Selectivity of odorant-binding proteins from the southern house mosquito tested against physiologically relevant ligands - Yin, Jiao; Choo, Young-Moo; Duan, Hongxia; Leal, Walter S. (Frontiers in Physiology, 2015)
As opposed to humans, insects rely heavily on an acute olfactory system for survival and reproduction. Two major types of olfactory proteins, namely, odorant-binding proteins (OBPs) and odorant receptors (ORs), may contribute to the selectivity and sensitivity of the insects’ olfactory system. Here, we aimed at addressing the question whether OBPs highly enriched in the antennae of the southern house mosquito, Culex quinquefasciatus, contribute at least in part to the selective reception of physiologically relevant compounds. Using a fluorescence reporter and a panel of 34 compounds, including oviposition attractants, human-derived attractants, and repellents, we measured binding affinities of CquiOBP1, CquiOBP2, and CquiOBP5. Based on dissociation constants, we surmised that CquiOBP2 is a carrier for the oviposition attractant skatole, whereas CquiOBP1 and CquiOBP5 might transport the oviposition pheromone MOP, a human-derived attractant nonanal, and the insect repellent picardin. Binding of these three ligands to CquiOBP1 was further analyzed by examining the influence of pH on apparent affinity as well as by docking these three ligands into CquiOBP1. Our findings suggest that CquiOBP1 might discriminate MOP from nonanal/picaridin on the basis of the midpoint transition of a pH-dependence conformational change, and that MOP is better accommodated in the binding cavity than the other two ligands. These findings, along with previous experimental evidence suggesting that CquiOBP1 does not detect nonanal in vivo, suggest that OBP selectivity may not be clearly manifested in their dissociation constants.